AN ANALYSIS OF STUDENT SPEAKING SKILL USING ROLE PLAY METHOD - Fifa Lestari (IKIP Siliwangi, 2020)
One of the skills that must be mastered in learning English is speaking. However, many people do not have the confidence to speak English because of several problems, both in grammar, vocabulary, pronunciation or fluency. One of the many methods that can improve speaking skills is role-playing. The purpose of the study is to find out whether role-playing techniques can improve students' speaking skill or not. It turns out that from several opinions of students that the speaking skills of students can practice pronunciation, and can increase vocabulary. Based on the data, it can be concluded that role-playing techniques can improve students' speaking skills. Keywords: Speaking Skills, Role Play